Elements of civil engineering and engineering mechanics - Raikar, R.V (PHI Learning, 2011)
This book equips the students with the basic knowledge of certain facets of Civil Engineering and Engineering Mechanics as needed by them in the beginning of their engineering education. The book is primarily tailored to conform to the first-year B.Tech syllabus of Visvesvaraya Technological University (VTU). It will be useful for the students in other universities too.